THE ENDOVASCULAR PREVENTION OF THROMBOEMBOLISM IN ATRIAL FIBRILLATION - Rami N. Al-Ayyubi; Evgeny V. Merkulov; Andrey S. Tereschenko; Dmitry V. Pevzner; Natalia S. Zhukova; Anatoly N. Samko; Ruslan V. Guchaev («REMEDIUM GROUP» Ltd., 2018)
The article dwells upon the various strategies for prevention of thromboembolic events in patients with atrial fibrillation. The main focus is put on the endovascular strategies for prevention of tromboembolism. In recent years, the endovascular strategies for the prevention of thromboembolic events in patients with atrial fibrillation, who have contraindications to oral anticoagulant therapy, are increasingly gaining popularity and find evidence of its safety for the prevention of thromboembolism. The patients with AF with a high risk of bleeding is the most interesting category for studying. The large studies confirm the effectiveness of non-drug prevention of thromboembolic events as compared to the anticoagulant therapy in these patients.